HUBUNGAN STRATEGI PENGAMPU TAHFIDZ DENGAN KETERCAPAIAN TARGET HAFALAN DI SMP IT INSAN KAMIL KARANGANYAR - Marfuah, Siti; Sukari, S; Amin, Lailla Hidayatul (Al’ulum Jurnal Pendidikan Islam, 2024)
In tahfidz learning, the strategies and approaches used by ustadz/ustadzah tahfidz master have a vital role to achieve the target of rote participants. The research aims to (1) recognizing the strategy employed by ustadz/ustadzah (2) knowing the memorized target of classroom viii educated at the junior high it insan kamil karanganyar; (3) knowing the relationship of the strategy employed by ustadz ustadzah the tahfidz light with the modern target of memorizing the eighth class protege at the junior high it insan kamil karanganyar. The study is correlation research aimed at proving the extent of the relation between variables and others. Data retrieval using frame and documentation. The analysis technique used in testing a hypothesis is a product correlation test. Research indicates that (1) ustadz/ustadzah tahfidz proficiency is zoned by a medium percentage of 33.92%; (2) research on memorizing target viii at high school it insan kamil karanganyar is categorized under a 33.92% percentage; (3) there is a significant influence on the strategy ustadz/ustadzah a tahfidz instrument with the modern target of rote participation. It can be proved by a hypothetical test using a product correlation formula of 0.774, it is in a strong category. In tahfidz learning, the strategies and approaches used by ustadz/ustadzah tahfidz master have a vital role to achieve the target of rote participants. The research aims to (1) recognizing the strategy employed by ustadz/ustadzah (2) knowing the memorized target of classroom viii educated at the junior high it insan kamil karanganyar; (3) knowing the relationship of the strategy employed by ustadz ustadzah the tahfidz light with the modern target of memorizing the eighth class protege at the junior high it insan kamil karanganyar. The study is correlation research aimed at proving the extent of the relation between variables and others. Data retrieval using frame and documentation. The analysis technique used in testing a hypothesis is a product correlation test. Research indicates that (1) ustadz/ustadzah tahfidz proficiency is zoned by a medium percentage of 33.92%; (2) research on memorizing target viii at high school it insan kamil karanganyar is categorized under a 33.92% percentage; (3) there is a significant influence on the strategy ustadz/ustadzah a tahfidz instrument with the modern target of rote participation. It can be proved by a hypothetical test using a product correlation formula of 0.774, it is in a strong category.